The Influence of Celebrity Endorsement, Brand Image, and Customer Satisfaction on the Sales of Kanky Shoes Products in the TikTok Shop - Muhammad Husin Nur Muzakki; Netta Belliawan Nikmah; Muhammad Kevin (Journal of Innovation, Business Management and Entrepreneurship, 2025)
The evolution of social media has given rise to new phenomena in the world of marketing, one of which is the emergence of the TikTok Shop platform, successfully capturing the attention of the public, especially the younger generation. Kanky shoes, as a local product, are trying to leverage this trend through digital marketing strategies such as the use of celebrity endorsement, strengthening brand image, and enhancing customer satisfaction. This research aims to determine the influence of Celebrity Endorsement (CE), Brand Image (BI), and Customer Satisfaction (CS) on the sales of Kanky shoes in the TikTok Shop marketplace. The study involved 87 respondents who are active TikTok Shop consumers. Data were analyzed using SPSS with normality tests, multiple linear regression, partial tests (t-test), and simultaneous tests (F-test). The results of the study indicate that all three independent variables have a significant influence, both partially and simultaneously, on sales. This research provides both theoretical and practical contributions to understanding effective digital marketing strategies in the social media era.